2020
DOI: 10.1007/s13300-020-00825-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ramadan on Physical Activity and Sleeping Patterns in Individuals with Type 2 Diabetes: The First Study Using Fitbit Device

Abstract: Introduction: The impact of Ramadan fasting, a type of intermittent fasting, on the management of diabetes has not been well investigated. Physical activity, sleep duration, and time of sleep are susceptible to alterations during Ramadan due to the changes in the times and numbers of meals. This study compared physical activity and sleep patterns of individuals with type 2 diabetes mellitus (T2DM) during and after Ramadan using the international physical activity questionnaire (IPAQ) and a Fitbit Flex 2 accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 65 publications
(72 reference statements)
1
29
0
Order By: Relevance
“…Though RF is generally obligatory for Muslims, many studies have reported the benefits of RF. Studies have analyzed the effect of RF in patients with various conditions, such as diabetes [ 12 , 13 ], kidney-related problems [ 14 ] and asthma [ 15 ]. In patients, RF should be carefully monitored by health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Though RF is generally obligatory for Muslims, many studies have reported the benefits of RF. Studies have analyzed the effect of RF in patients with various conditions, such as diabetes [ 12 , 13 ], kidney-related problems [ 14 ] and asthma [ 15 ]. In patients, RF should be carefully monitored by health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Ramadan intermittent fasting is a safe lifestyle modification that involves specific dietary and lifestyle modifications, such as changes in food quantity and quality, nocturnal food consumption, meal frequency, and sleep cycle as well as reduction in exercise [ 11 14 ]. Ramadan fasting has been associated with variable weight changes, ranging from a modest weight gain to weight neutrality and weight loss [ 15 ], with a reported reduction in total calorie intake in some [ 16 ], but not all populations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, people could be encouraged to practice home exercise, such as stretching, walking, and strengthening. A recent study reported that type 2 diabetics from Saudi Arabia displayed low physical activity and poor sleep behaviors during Ramadan [70].…”
Section: Rf and Exercisementioning
confidence: 99%